Treatment of insomnia in myasthenia gravis—A prospective study on non-benzodiazepine hypnotics in the treatment of myasthenia gravis patients with insomnia - Yan, Jingwen; Yang, Minhui; Li, Michael Ke; Huang, Yangyu; Tan, Ying; Shi, Jiayu; Fan, Qianqian; Zhu, Zhu; Guan, Yuzhou; Cui, Liying (Frontiers in Neurology, 2023)
Objectives This study aimed to evaluate the efficacy and safety of non-benzodiazepine hypnotics in the treatment of myasthenia gravis (MG) patients with insomnia. Methods This is a prospective longitudinal study. Outpatients who met the criteria for stable MG and insomnia diagnosis according to the International Classification of Sleep Disorders (third edition) were included in the study. They took a regular dose of non-benzodiazepine hypnotics (zolpidem 10 mg per night or zopiclone 7.5 mg per night) based on their own preferences. Patients received psychotherapy (including sleep health education) and were followed up for 4–5 weeks. Cases with lung diseases, respiratory disorders, or inappropriate use of hypnotic medications were excluded. The primary outcome is the difference in total Pittsburgh Sleep Quality Index (PSQI) score between baseline and the end of follow-up period. Secondary outcomes include the difference in Myasthenia Gravis Activities of Daily Living (MG-ADL) score, 7-item Generalized Anxiety Disorder Questionnaire (GAD-7), and the Patient Health Questionnaire-9 (PHQ-9) between baseline and the end of follow-up period and the safety of medication. Results A total of 75 MG patients with insomnia were included in this study. After 4–5 weeks of treatment, the total PSQI score and MG-ADL score were lower than baseline (p < 0.01). No patients had an increased MG-ADL score. The incidence rate of adverse events was 16.0% (12 cases), including dizziness (6 cases, 8.0%), drowsiness (3 cases, 4.0%), fatigue (2 cases, 2.7%), and nausea (1 case, 1.3%), all of which were mild. No patients had new onset breathing disorders. Conclusion Non-benzodiazepine hypnotics are safe and effective for stable MG patients who need insomnia treatment.